2016
DOI: 10.1016/j.bej.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Production of sophorolipids from winterization oil cake by solid-state fermentation: Optimization, monitoring and effect of mixing

Abstract: Sophorolipids (SLs) are a group of extracellular biosurfactants produced by the yeast Starmerella bombicola. The present study explored the use of winterization oil cake (WOC), a residual oil cake that comes from the oil refining industry, as a substrate for the production of SLs by solid-state fermentation (SSF). Sugar beet molasses (MOL) was used as a co-substrate and C. bombicola ATCC 22214 as the inoculum. Fermentation was performed on the 100-g scale and was optimized in terms of the ratio of substrates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 23 publications
7
63
1
2
Order By: Relevance
“…The structural characterization of the produced SL extracts was confirmed by the FT-IR and 1H NMR analyses which was in agreement with Rashad et al, (2014 a and b) and Jiménez-Peñalver et al (2016). According to the results of the FT-IR and 1 HNMR analyses, all these structural features further confirmed the existence of SL groups in the isolated compounds (acidic and lactone ring form).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The structural characterization of the produced SL extracts was confirmed by the FT-IR and 1H NMR analyses which was in agreement with Rashad et al, (2014 a and b) and Jiménez-Peñalver et al (2016). According to the results of the FT-IR and 1 HNMR analyses, all these structural features further confirmed the existence of SL groups in the isolated compounds (acidic and lactone ring form).…”
Section: Resultssupporting
confidence: 88%
“…Lower yield was also reported (23.5 g·100 g −1 dry matter) for the production of SLs using the SSF of sunflower winterization oil cake plus sugar beet molasses by Starmerella bombicola ATCC 22214 (Jiménez-Peñalver et al, 2016). The yield obtained in this study was also higher than that produced by Parekh and Pandit (2012), who found that the SSF of glucose, wheat bran and oleic acid by Starmerella bombicola NRRL Y-17069 produce a maximum SL yield of 18g per 100g substrate.…”
Section: Resultsmentioning
confidence: 89%
“…Oxygen mostly comes from the gas phase and also from that dissolved in water due to growth and metabolism of the culture [126]. However, compared to SMF, in SSF, gas transfer is much higher due to high interfacial area-to-liquid volume ratios of solid substrate particles [128][129][130]. During the fermentation process, the microorganism consumes oxygen, decreasing oxygen concentrations.…”
Section: Bioreactor Type Features/problemsmentioning
confidence: 99%
“…Levels become less and less along the penetration depth, possibly reaching zero at a certain depth. Increasing oxygen transfer can increase penetration depth of the mycelium [130]. Gas volume within solid substrate particles inside bioreactors represents the void fraction.…”
Section: Bioreactor Type Features/problemsmentioning
confidence: 99%
“…Maximum yield of sophorolipids (18 g·mg −1 dry substrate) was attained by the cultivation of Starmerella bombicola on a mixture of wheat bran, glucose and oleic acid [176]. It was reported that by employing an intermittent mixing in SSF during the fermentation the production of sophorolipids increased in a 31% [177]. Moreover, the cultivation of Pseudomonas aeruginosa on a mixture of sugarcane bagasse and corn bran supplemented with glycerol and soybean oil in SSF produced 45 g·L −1 of rhamnolipids [178].…”
Section: Biosurfactant Productionmentioning
confidence: 99%